The Role of Faith-Based Coping Mechanisms in Enhancing Mental Resilience: A Study Among Muslim Students - Shehar Bano; Waqeem Akram; Umm E Habiba; Hafsa Arshad (Research Journal of Psychology, 2025)
Students’ mental health issues have received a lot of attention around the world. In this respect, religious beliefs, especially from students of the Islamic faith have benefits in boosting the ability to cope with stress and other mental conditions. More information about how Islam helps with mental health is explained in this article such as praying, reciting the Quran, having family and friends, and relying on Allah (Tawakkul). Most of the findings provide support for the use of faith-based models in psychological therapies, especially in the formulation of an integrated package of care for psychologists’ clients. In this research, the scholars intend to explore how Salah, (prayers) and reading the Quran improve mental health among students. An exploratory cross-sectional survey research design using both quantitative and qualitative data was employed to analyze the effects on stress coping and mental health of these religious practices. Questions posed to the participants included the number of times they performed Salah, reading of the Quran, and other religious-related activities used to address stress. It also examined practitioners’ endowed impressions of how efficacious such practices are for fostering psychological fortitude and incorporated queries regarding the way faith may facilitate overcoming mental illness in the Self-Reflexive portion. The study hypothesized was that religious practices such as Salah, and Quranic recitation improve the psychological well-being of Muslim students. The survey asked participants to rate these practices on the scale and free comments indicated how faith helps people cope with emotions, stress, and other challenges. As the results pointed their finger to the positive relationship between increased regular religious attendance on stress-related coping, the present findings are consistent with the other research evidencing the salutary effects of spirituality on mental health. It emerged that faith-based practices enable Muslim students to persevere in issues aching their academic or social lives. However, participants also expressed difficulties in sustaining such practice during certain periods, for example, time pressure or limited resources. The work indicates that the adaptation of religion-based values into university counseling services may be helpful in addressing the psychological needs of Muslim students. In addition, the current study urges subsequent studies to look at the part that Imams, Chaplains, and self-help groups can jointly play in improving the psychological well-being of Muslim students. I can safely assume that by incorporating religious concepts into models of support for mental health, universities may adapt better to the currently diverse student rolls.